Etherification optimization for preparing partially hydrolized hydroxypropylated guar gum and its properties. Issue 13 (11th February 2014) - Hongbo, Tang; Yanping, Li; Siqing, Dong; Min, Sun
ABSTRACT The partially hydrolized hydroxypropylated guar gum (PHHGG) was prepared using GG as the raw material, hydrochloric acid as the hydrolysis agent, epoxy propane as the etherifying agent, ethanol as the solvent to obtain better property combination. The effect of the reaction temperature, reaction time, and amounts of sodium hydroxide, ethanol, and epoxy propane on the substitution degree of the partially hydrolized hydroxypropylated GG was investigated. These process parameters were optimized by the orthogonal test. Using polarized light microscopy, infrared spectrometer, differential scanning calorimetry, and thermogravimetric analyzer, the appearance, structure, and thermal property of the partially hydrolized hydroxypropylated GG (PHHGG) were observed and measured. The results indicated that the best process conditions for preparing the PHHGG were: reaction temperature = 60°C, reaction time = 12 h, amount of sodium hydroxide = 1.2%, amount of ethanol = 60%. The acid resistance and alkali resistance of GG were obviously improved by the acidolysis and hydroxypropylation. The particle appearance of GG was a thin strip after it was hydrolized by acid and hydroxypropylated by epoxy propane. The acidolysis increased the melting onset temperature, peak temperature, and end temperature of GG but the hydroxypropylation decreased them. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40489.